Young driver risk factors: successful and unsuccessful approaches for dealing with them and an agenda for the future - Williams, A F (BMJ Group, 2006)
The extent to which various interventions to deal with the young driver crash problem have worked are discussed, and promising interventions that should be tried are identified. Traditional forms of driver licensing and driver education have not worked. Graduated licensing reduces the problem and existing laws need to be strengthened. Programs involving parents and police have shown some potential to increase compliance with graduated licensing restrictions. Insurer discount programs also have potential. In other public health areas, comprehensive programs have worked better than those based on single components. There are continuing efforts to develop new driver education and training programs and methods of delivery that can combine with graduated licensing and contribute to reductions in the young driver problem. The most promising intervention strategy is likely to be a coordinated community based program in states with strong graduated licensing laws as a foundation, involving modern education and training techniques, insurance discount programs, and well publicized enforcement and education programs featuring parents and police in combination, with as much input and participation as possible from the target group of young drivers.